Strategy and business process management : techniques for improving execution, adaptability, and consistency - Lehmann, Carl F.; Kutnick, Dale. (Boca Raton : Taylor & Francis, 2012)
"Preface ABOUT THIS BOOK Running a business often requires leaders and management teams to do things better and faster with fewer resources and at lower cost. Some organizations always seem to adapt and flourish at this and others struggle. Why? Those that succeed do so because they always look at how they do things and continuously ask, "How can we run our business better?" They answer the question by first learning the best practices of other highly successful organizations. Next, they look inward, studying how they currently do things. They then take what they've learned and experiment with changes, testing new ways to work smarter, better, and faster at lower cost using the resources at hand. But doing this requires research, knowledge, planning, and tools. Proficiency and skills must be garnered from several disciplines that include the following - Crafting and adapting a competitive and defensible business strategy - Translating business strategy into action - Empowering and motivating the workforce - Designing effective and efficient business processes - Implementing information technology for cost-effective execution - Aligning resources such as people, processes, and technology to consistently execute business strategy Execution requires mastery of several skills including the following: - Insightful leadership capable of orchestrating a multidisciplinary management team"--
section 1. Best practices used in strategic planning -- section 2. Execution : best practice use of strategic resources -- section 3. How to align strategy and resources to improve execution, adaptability, and consistency -- section 4. Summary conclusion.
"An Auerback Book."
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Strategic planning; Management; Business logistics; Electronic books